KONSERVASI TRADISIONAL TERHADAP SUMBER DAYA ALAM DI OHOI ELAAR LAMAGORANG KECAMATAN KEI-KECIL TIMUR SELATAN KABUPATEN MALUKU TENGGARA - Mei Endang Warbal; Ernywati Badaruddin; Maya M. S. Puttileihalat (MARSEGU : Jurnal Sains dan Teknologi, 2025)
This study aims to determine the forms of traditional conservation and the process of implementing traditional preservation of natural resources in Ohoi Elaar Lamagorang, Kei-Kecil Timur Selatan District, Southeast Maluku Regency. The method used is descriptive by making systematic and accurate descriptions according to the facts in the field and reviewing the norms applied in implementing traditional conservation. Data were obtained through interviews, observations, and documentation. The results of the analysis show that the Ohoi Elaar Lamagorang community still practices various forms of traditional conservation such as the sasi (huwear) system, a ban on indiscriminate tree felling, the obligation to replant, and hereditary management of the hamlet. Customary values ​​and spirituality are a strong foundation in maintaining the sustainability of natural resources. However, modernization and economic pressures are the main challenges in preserving traditional conservation. Strengthening of customary institutions and integration of local wisdom in natural resource management policies are needed.